Pengaruh kepuasan kerja dan komitmen organisasi terhadap organizational citizenship behavior karyawan - Retty Rizda Ismaillah; Hendro Prasetyono (Universitas Indraprasta PGRI, 2021)
Organizational Citizenship Behavior is currently a concern of organizational leaders around the world. This study aims to determine the effect of job satisfaction and organizational commitment to Organizational Citizenship Behavior partially and simultaneously. The research method used is quantitative research with survey methods. The sampling technique is a saturated sample that uses the entire population of employees in the Blood Transfusion Unit of the Indonesian Red Cross Center of 78 people. Data collection techniques use questionnaires compiled from the development of dimensions of each variable in the study. Data analysis techniques begin with normality tests, homogeneity tests and multiple regression analysis with the help of SPSS version 23.0. The results showed that there was a positive and significant influence on job satisfaction variables on organizational citizenship behavior. Organizational Commitment variables have a positive and significant effect on Organizational Citizenship Behavior. Simultaneously,the variables of Job Satisfaction and Organizational Commitment have a positive and significant effect on Organizational Citizenship Behavior. The pathway coefficient indicates that organizational commitment contributes more than job satisfaction to Organizational Citizenship Behavior. This has implications for leaders or managers must increase employee commitment so that Organizational Citizenship Behavior increases. The limitation in this study is the research sample only from the Indonesian Red Cross in the Jakarta Branch. Further research is needed to take samples of employees from several other branches of the Indonesian Red Cross to really know the real condition.